2016
DOI: 10.1007/s10482-016-0771-9
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas and Plesiomonas species from scarlet ibis (Eudocimus ruber) and their environment: monitoring antimicrobial susceptibility and virulence

Abstract: The present study aimed at evaluating the role of captive scarlet ibises (Eudocimus ruber) and their environment as reservoirs of Aeromonas spp. and Plesiomonas spp., and analyzing the in vitro antimicrobial susceptibility and virulence of the recovered bacterial isolates. Thus, non-lactose and weak-lactose fermenting, oxidase positive Gram-negative bacilli were recovered from cloacal samples (n = 30) of scarlet ibises kept in a conservational facility and from water samples (n = 30) from their environment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…To date, they have been shown to infect a vast number of hosts, including fish, domestic chickens, lower and higher vertebrates, and humans. [1][2][3] In animals, Aeromonas species cause illnesses ranging from furunculosis and diarrhea to septicemia. 4 However, because of the wile use of broad-spectrum antibiotics in clinical settings, agriculture, and aquaculture, there has been an increase in antibiotic resistance among disease-causing Aeromonas species.…”
Section: Introductionmentioning
confidence: 99%
“…To date, they have been shown to infect a vast number of hosts, including fish, domestic chickens, lower and higher vertebrates, and humans. [1][2][3] In animals, Aeromonas species cause illnesses ranging from furunculosis and diarrhea to septicemia. 4 However, because of the wile use of broad-spectrum antibiotics in clinical settings, agriculture, and aquaculture, there has been an increase in antibiotic resistance among disease-causing Aeromonas species.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that in the 2015/2016 breeding season, some cloacal samples of scarlet ibis did not show any bacterial growth, while in the 2016/2017 season, at least two isolates were identified in each of the samples. Castelo-Branco et al (14) observed that in scarlet ibis, habitat and feeding could be responsible for the bacteriological composition, which reinforces the importance of environmental monitoring. Five genera of bacteria were observed in total.…”
Section: Discussionmentioning
confidence: 86%
“…Castelo-Branco et al (2017) (14) examined whether captive scarlet ibis (Eudocimus ruber) in Mangal das Garças Park (Belém-PA) are reservoirs and carriers of Aeromonas spp. and Plesiomonas spp.…”
Section: Scarlet Ibis (Eudocimus Ruber) Is a Waterbird Of The Order Pmentioning
confidence: 99%
See 2 more Smart Citations